Visionary Leadership Strategy to Enhance Teacher Creativity at Darul Hikmah Islamic Boarding School Tulungagung - Haryanti, Nik; Saerozi, Imam (STKIP PGRI SITUBONDO, 2024)
This study examines the visionary leadership strategy in enhancing teacher creativity at Darul Hikmah Islamic Boarding School, Tulungagung. The research is motivated by the phenomenon of the kiai as the pesantren leader, representing a unique and compelling form of leadership. The research approach employs a qualitative method. Data collection techniques include participant observation, in-depth interviews, and documentation. The data analysis techniques used are: 1) data condensation, 2) data display, and 3) conclusion drawing/verification. Based on the results of this study, it can be concluded that visionary leadership is carried out by the kiai acting as a direction-setter, agent of change, supervisor, and role model, embodying ruh al-jihad and the spirit of striving to advance Darul Hikmah through the formation of a team in the management of the educational institution and collaboration with external parties in learning activities. The visionary leadership strategy in enhancing teacher creativity at Darul Hikmah Islamic Boarding School, Tulungagung consists of: a) The kiai as a direction-setter communicates the vision to all components of the pesantren both horizontally and vertically. b) The kiai at Darul Hikmah Islamic Boarding School, Tulungagung serves as an agent of change responsible for inspiring transformation within the pesantren by teaching both religious and general knowledge to prepare and shape a young generation with strong religious insight and high intellectual capacity. c) The kiai as a good mentor fosters teamwork in realizing the vision and mission of Darul Hikmah by forming a team for educational institution management and collaborating with external parties in learning activities. d) The kiai as uswatun hasanah or a good role model demonstrates ruh al-jihad and the spirit of striving to develop and advance Darul Hikmah Islamic Boarding School.